De novo genome assembly of Cercospora beticola for microsatellite marker development and validation. (April 2017) - Vaghefi, Niloofar; Kikkert, Julie R.; Bolton, Melvin D.; Hanson, Linda E.; Secor, Gary A.; Pethybridge, Sarah J.
Abstract: Cercospora leaf spot caused by Cercospora beticola is a significant threat to the production of sugar and table beet worldwide. A de novo genome assembly of C. beticola was used to develop eight polymorphic and reproducible microsatellite markers for population genetic analyses. These markers were used, along with five previously described microsatellite loci to genotype two C. beticola populations from table beet fields in New York, USA. High allelic and genotypic diversity and low population differentiation were found between fields. Linkage disequilibrium of loci after clone-correction of datasets was attributed to the presence of two distinct clonal lineages within the populations. Linkage equilibrium of loci in one of the clusters supported the presence of sexual reproduction. The draft de novo genome assembly will help elucidate the reproductive system of C. beticola through investigating evidence of recombination in the C. beticola genome.